1987
DOI: 10.1002/ddr.430100304
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies on factors influencing the collecting phase of the cystometrogram in urethane‐anesthetized rats

Abstract: Maggi, C.A., P. Santicioli, and A. Meli: Pharmacological studies on factors influencing the collecting phase of cystometrogram in urethane-anesthetized rats. Drug Dev. Res. The effect of various pharmacological interventions on the collecting phase of cystometrogram (CMG) has been investigated by means of a new cystometric procedure in urethaneanesthetized rats. The method involves the transvesical infusion, through a needle inserted in the bladder dome, of warm (37OC) saline at a rate (2.8 mllh) simulating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Animal studies have shown that the sympathetic input to the bladder is tonically active during filling (Edwardsen, 1968; de Groat & Lalley, 1972; Satchell & Vaughan, 1988). Furthermore, hypo‐gastric nerve section, ganglionic blockade and β‐adrenoceptor blockade produce decreases in bladder compliance, bladder capacity and volume threshold for micturition, consistent with a sympathoinhibitory tone to the bladder during filling (Maggi et al , 1987; Flood et al , 1988; Vaughan & Satchell, 1992). It has recently been proposed that the sympathoinhibitory drive to the bladder partially reduces the level of bladder wall tension transduced by the bladder wall mechanoreceptors, and thus delays the time at which micturition threshold is attained (Vaughan & Satchell, 1995).…”
Section: Discussionmentioning
confidence: 78%
“…Animal studies have shown that the sympathetic input to the bladder is tonically active during filling (Edwardsen, 1968; de Groat & Lalley, 1972; Satchell & Vaughan, 1988). Furthermore, hypo‐gastric nerve section, ganglionic blockade and β‐adrenoceptor blockade produce decreases in bladder compliance, bladder capacity and volume threshold for micturition, consistent with a sympathoinhibitory tone to the bladder during filling (Maggi et al , 1987; Flood et al , 1988; Vaughan & Satchell, 1992). It has recently been proposed that the sympathoinhibitory drive to the bladder partially reduces the level of bladder wall tension transduced by the bladder wall mechanoreceptors, and thus delays the time at which micturition threshold is attained (Vaughan & Satchell, 1995).…”
Section: Discussionmentioning
confidence: 78%
“…Through a midline inci sion of the abdomen, the urinary bladder was exposed and the vesical dome apex was cannulated. This method permits to record storage and voiding phases of the bladder [8]. The catheter was connected both to an infusion pump and a pressure transducer.…”
Section: Methodsmentioning
confidence: 99%
“…Effects of GS-332 on micturition intervals and micturition reflex in anesthetized rat cystometory Experiment was performed according to the method of Maggi et al, 1987 (Japan). GS-332 and clenbuterol were dissolved in distilled water, and SR59230A was dissolved in DMSO.…”
Section: Animalsmentioning
confidence: 99%